An investigation into the prevalence of diabetes in the Northwest of Iran: The case study of Maragheh City - asadianfam, shiva; Abdollahi, Nasibeh (Archives of Medical Laboratory Sciences, 2019)
Background: Diabetes is a type of metabolic diseases whose common characteristic is the increase in blood sugar. The prevalence of diabetes worldwide has progressively reached epidemic proportions. Its complications are microvascular and macrovascular complications, gastrointestinal and genitourinary disorders, infection and glaucoma. This study was designed to examine the incidence of diabetes in case of gender and age differences, and to investigate its complications .to better understand related etiology. Materials and Methods: This research was a cross-sectional study undertaken on 380 diabetic patients referred to Amir-al-Momenin Hospital in Maragheh. The data were collected using patient records and analysed using SPSS software. The frequency and frequency percent of the qualitative data and the mean of the quantitative data were reported. Results: The analysis suggested that among 380 diabetic patients, 248 were female and 132 were male, and 95.3% of those surveyed were married. The mean age of the patients under investigation was 57.66. 303 patients (79.7%) of the participants had a history of drug use, and the drugs are mainly cardiovascular drugs (35.8%), metformin (33.9%), and glibenclamide (28.2%). Over 50% of the participants had a history of illness, particularly cardiovascular disease (48.2%), while the least number of the participant had seizures. The highest and lowest number of patients had the blood sugar range of 424-325 (84 patients, 22.1%) and the blood sugar range of 622-523 (17 patients, 4.5%) , respectively. Moreover, the largest number of subjects (65 patients, 17.1%) had the blood cholesterol in the range of 325-271. About 75 participants had too much LDL. Besides, no statistically significant relationship was found between diabetes and white blood cells . 172 subjects developed complications. 70 patients, 68 patients, 55 patients, 51 patients, 14 patients, 13 patients, and 5 patients had renal, gastrointestinal, cutaneous, respiratory, cardiovascular, ocular complications, and amputations, respectively. About 110 subjects had various habits such as special diet (n = 44), smoking (n = 39), addiction (n=26) and drinking (n=3). Among 11 subjects of gestational diabetes mellitus (GDM), most had a high body mass index (BMI), the protein in the urine of about 18 percent of the subjects was positive, and regarding glucose disposal in the urine, 53 subjects were +, 64 subjects were +, 42 subjects were +++, 1 subject was ++++. Seventy participants had ketone disposal, which indicates kidney disorder. Conclusion: The results revealed a higher prevalence of disease among middle-aged and older people in the society. The mean of B.M.I is 27.28 showing overweight in our population. The results also indicated a higher prevalence of hyperglycemia compared to hypoglycemia that may be due to very close relationship between diabetes and cardiovascular disorders, high levels of blood sugar in most of the diabetic patients. In addition, in a large number of fat people or people with hyperlipidemia were diabetic. In order to decrease mortality, and to diminish direct and indirect costs of diabetes, it is required to take essential measures. Such measures can include effective approaches to inform people for importance of nutrition education programs in controlling blood sugar and fat in diabetic patients via mass media and different programs.